Study on the genetic diversity of wax trees (Rhus succedanea L.) in Northern mountainous region of Vietnam by SSR and SCoT markers - Hong Chien, Nguyen; Thi Kim Linh, Nguyen; Thi Kim My, Trin; Xuan Truong, Nguyen; Van Chung, Nguyen; Thi Trang, Le; Huu La, Nguyen (Vietnam Journal of Biotechnology, 2021)
Wax tree has been cultivated to get lacquer, a valuable source of material that is necessary for many industries and handicrafts. Evaluating not only phenotype but also genotype is essential in order to increase the efficiency of new breeding program. In this study, the genetic relationship at the molecular level of 90 wax trees collected in three regions, i.e., Tam Nong, Thanh Son (Phu Tho) and Chiem Hoa (Tuyen Quang), was analyzed by SSR and ScoT markers. The results revealed a significant diversity among the individuals, with similarity coefficient from 0.41 to 0.98. The sample group collected in Chiem Hoa was significantly different from that in Tam Nong. Most of samples which had a high level of genetic similarity, from 0.95 to 0.98, were pairs of samples at the same geographical origin. The high similarity degree of these samples is likely due to the practice of selecting seeds from high-yield wax tree to be kept for seeds. These results provide the necessary information for new wax tree breeding program.